KELELAHAN KERJA PADA OPERATOR CONTAINER CRANE DI PT. X - Nesya Yulita Anindya (Universitas Airlangga, 2018)
Fatigue that caused by working activity is a problem which every workers had already experienced it. Fatigue condition that happened on workers usually occurs differently. Fatigue that caused by working activity had some determinant factors. Container Crane operator was a job that had an important role on container handling process at PT. X. This handling process occurred 24 hours/day, and divided into 3 shift work morning, evening and night shift. Two operator operated a CC for every 8 work hour by turns. The purpose of this research was to describe fatigue that caused by working activity on CC operator at PT. X. This research was a observational descriptive study that describe work fatigue that caused by working activity and determinant factor on container crane operators. Population of this research was all 51 CC operators. Descriptive analytic showed in form of frequency, percentage, and cross tabulation. The result showed that fatigue on CC operators mostly was a low fatigue level (90.2%), and the rest (9.8%) was a medium fatigue level. Workers that experienced medium fatigue level mostly on evening shift (40%) Night shift workers tend to experienced fatigue that caused by working. Lenght of sleep time ≤6.5 hours tend to experienced fatigue caused by working.Keywords: fatigue work, operator, shift work